Pressure, pleasure and function: Malaysian undergraduates reading across boundaries in a university in England - Chong, S.L. (Taylor and Francis, 2018)
In this chapter, I discuss part of an in-depth empirical study that I carried out for my doctoral research, which aimed to understand how Malaysian undergraduates in an English university experienced reading. In my study, I contrasted these undergraduatesâ perspectives on their past contexts in school with current contexts in the university to show up complex relationships of what it means to read. My 167exploration of this complexity showed how the reading experience, when seen through the readerâs eyes, can contradict and challenge conventional wisdom of what it means to read for pleasure, for functional purposes or under pressure. My study also offers empirical evidence showing how even within boundaries of reading genres and formal spaces, the reader is fundamentally his or her own agent of change. Therefore, if research helps us to see reading experiences as more fluid than hitherto, it also means we need to expand our conception of literacy. Â© 2018 selection and editorial matter, Evelyn Arizpe and Gabrielle Cliff Hodges; individual chapters, the contributors.